Reconstructing the Character Building of Leaders from Islamic and Pancasila Perspectives - Muh , Tabran; Umar, Umar; Maknun , Lu'luil (Universitas Muhammadiyah Surakarta, 2025)
Pancasila serves as the ideological and ethical foundation for leadership, aiming to shape leaders with integrity and morality grounded in divine, humanitarian, unity, civic, and social justice values harmonizing with Islamic leadership principles. This study uses a qualitative and normative (doctrinal) method, focusing on the philosophical and conceptual foundations of Pancasila. Data were collected through bibliographic research, analyzing books, journals, and previous studies to build a strong theoretical framework. The findings reveal that the de-ideologization of Pancasila’s leadership ethics stems from weak political systems, ineffective oversight, and the failure of character education based on Pancasila values. These issues undermine public trust and threaten national stability. Pancasila thus functions as both a moral fortress against ideological distortion and a benchmark distinguishing leaders guided by Pancasila values from those driven by power. Practically, this research provides insights and guidance for ethical leadership practice. Theoretically, it contributes to leadership studies, particularly regarding the integration of Pancasila’s ethical and ideological dimensions in fostering just, moral, and responsible leadership.